Heart rate variability biofeedback increases sexual arousal among women with female sexual arousal disorder: Results from a randomized-controlled trial. (April 2019) - Stanton, Amelia M.; Boyd, Ryan L.; Fogarty, Justin J.; Meston, Cindy M.
Abstract: Low resting heart rate variability (HRV) has been associated with poor sexual arousal function in women. In a recent study, a single session of autogenic training increased HRV and facilitated improvements in both sexual arousal and perceived genital sensations among women experiencing decreased arousal. The current study expands upon these findings by examining the efficacy of HRV biofeedback, with and without autogenic training, as a treatment for sexual arousal dysfunction in an at-home setting. Participants ( N  = 78) were randomized into one of three conditions: HRV biofeedback, HRV biofeedback + autogenic training, or waitlist control. Each condition included three laboratory sessions; participants in the two active conditions completed 4–6 biofeedback sessions at home, and participants in the HRVB + A condition listened to a 14-min autogenic training recording before completing the biofeedback. Across the three laboratory visits, participants in the three conditions singficnatly differed in their genital arousal, subjective sexual arousal, and their perceived genital sensations. Compared to women in the control group, women who engaged in HRV biofeedback at home, with and without additional autogenic training, experienced increases in genital arousal, subjective sexual arousal, and perceived genital sensations. These results provide preliminary support for the contribution of heart rate variability level to female sexual arousal function and for the use of either of these interventions in the treatment of sexual arousal concerns. Highlights: Female sexual arousal dysfunction affects one out of every four women in the United States. Low heart rate variability has been associated with compromised arousal function in women. Targeting heart rate variability level in treatment increases sexual arousal in women with female sexual arousal disorder.